High-Skilled Inventor Emigration as a Moderator for Increased Innovativeness and Growth in Sending Countries - Jisong Kim; Nah Youn Lee (East Asian Economic Review (EAER), 2019)
This study investigates the effect of high-skilled inventor emigration rate on growth rate of the country of origin (COO). Inventor emigrants represent the human capital that can generate highly innovative work. The social network they form spurs knowledge diffusion and technology transfer back to their COOs, which in turn affects innovation and growth in their home countries. We run dynamic panel estimation for 154 countries during 1990–2011, and empirically show that a positive and statistically significant effect exists for the interaction of inventor emigration and trade. The result indicates that the direct negative impact of the brain drain can be mitigated by the positive feedback effect generated by the high-skilled inventor emigrants abroad. When coupled with an active trade policy that reinforces growth, countries can partially recoup the direct effect of the human capital loss. We stress the importance of international trade for successful technology transfer to occur, and offer insights for policies that can utilize the benefits of the rich social network of their high-skilled emigrants.
Keywords: O15; O33; O50; 330; High-skilled Inventor Emigration; Technology Transfer; Innovativeness; Growth Rate; Externalities; Networks